Hábitos alimenticios y ecología trófica del pez Lutjanus griseus(Pisces: Lutjanidae) asociado a la vegetación sumergida en la Laguna de Términos, Campeche, México - Guevara, Emma (2007)
In Campeche, Mexico, the Laguna de Términos has Thalassia testudinum beds inhabited by the grey snapper, Lutjanus griseus (Linnaeus 1758). Along one year, we collected 994 individuals and 672 had food in their stomachs; we recorded number, weight, and frequency of trophic groups, and the index of relative importance. Dominant food components were Farfantepenaeus duorarum and Palemonetes octaviae, Eucinostomus gula (Cuvier 1830) and Libinia dubia. Salinity and temperature were related to the number of individuals collected and with greater fish consumption by large L. griseus. The trophic niche breadth index was calculated for six size-classes of fish. The smallest and the largest fish had the lowest index values, whereas medium-size snappers had higher values. This snapper has a preference for habitats with submerged vegetation. The percentage of fish with food in their stomachs was higher during dark hours, providing evidence of the nocturnal habits of this fish.